Man one - Estleman, Loren D. (Estleman, Loren D. Amos Walker novels, 2026)
Young widow Sage Holland doesn't look like a murderer--and that's because she isn't one. The beautiful dame has driven non-stop from her home in frozen Alaska to seek out the services of private investigator Amos Walker, bringing not just the ice and snow with her. Sage has a stalker: her late husband's vengeful brother, who's determined to make her pay for a crime she didn't commit. Someone killed David, but it wasn't her. Walker is no fool. He knows not to take the words of husky-voiced, sorrowful women at face value. But Sage is in sore need of protection, and Walker's hunt for clues on Detroit's wintry streets soon leads to far more dead bodies than expected. He'll have to use every trick he's learned if he's to keep not just his client's blood, but also his own from staining the snow.